The role of perceived stress in the relation between childhood maltreatment and severity of alcohol use disorder: a mediation analysis - Bougelet, Emilie; Deffaa, Mirjam; Türkmen, Cagdas; Kiefer, Falk; Vollstädt-Klein, Sabine; Gerhardt, Sarah (European addiction research, 2024)
Introduction: Experiences of Childhood Maltreatment (CM) relate to relapse and lower treatment success in Alcohol Use Disorder (AUD), one of the most prevalent substance use disorders. However, the exact mechanisms of this relationship still remain unclear. This study examines perceived stress and “drinking to cope with negative affect” (coping) as possible mediators in this relationship. Moreover, it aims at uncovering the differential effects of the subtypes of CM. Methods:N = 96 individuals (42% women; mean age 41 ± 13 years) including healthy controls and individuals with varying severity of AUD and CM completed the Alcohol-Dependence Scale, Childhood Trauma Questionnaire, Perceived Stress Scale and German Inventory of Drinking Situations. Mediation analyses including perceived stress as a mediator between CM (and subtypes) and severity of AUD, as well as a serial mediation of the relationship between CM and AUD severity by perceived stress and coping were conducted. Results: Perceived stress significantly mediated the relation between CM and AUD severity and the serial mediation by perceived stress and coping turned out significant. Subtype-specific analyses did not yield significant results. Conclusion: This study reinforces perceived stress as a potential mechanism in the relation between CM and AUD severity. Moreover, coping further mediated the relationship between CM and AUD severity. Our results suggest including screening for CM (subtypes) in clinical routine in order to individually emphasize interventions focusing on stress regulation, as well as on developing healthy coping mechanisms, in patients with AUD. This might prevent heightened stress sensitivity, relapse and further maintenance of AUD.
Online veröffentlicht: 17. Juli 2024
Gesehen am 18.11.2024